The Ottoman tanbūr : the long-necked lute of Ottoman art music - Zeeuw, Hans de (Archaeopress Archaeology, 2022)
Tanbūrs are long-necked lute-like instruments played in the art, Sufi, and folk musical traditions along the Silk Road and beyond. This book provides a detailed study of the history of the tanbūr, its role in Ottoman music, construction and playing technique.